Ways to do philosophy in the imperial age: Alexander of Aphrodisias and his Commentary on the Topics - González Calderón, Juan Felipe (ΠΗΓΗ/FONS, 2019)
This paper intends to prove that Alexander of Aphrodisias’ exegetical method in his commentary on Aristotle’s Topics follows some of the procedures of exegesis successfully applied in the field of Philology. A close examination of the passages devoted to commenting the definition of syllogism will teach as Alexander’s overriding concern the explanation and clarification of the Stagirite’s exact terms and precise wording. Alexander’s interpretative framework is no other that the one provided by the Aristotelian corpus. Although through this method he was able both to establish conceptual connections and to propose innovative and influential theses, this very same method set the boundaries of his conception of logic.